New Society in John’s Gospel - Mullooparampil, Sebastian (Asian Horizons, 2010)
Thomas Vallianippuram, New Society in John’s Gospel, Aloor: Biblia Publications, 2008. Pages: xxx+479. ISBN: 81-87271-14-0.